The cognitive and personality profiles of individuals who request preditive testing for Huntington's disease - Lucas, Marilyn Doreen (My University, 2014)
Huntington's disease (HD), first described in 1872, is a progressive, debilitating, and ultimately fatal, neuropsychiatric genetic disorder. The discovery of a polymorphic DNA marker in 1983 closely localised HD to the short arm of chromosome 4, and the breakthrough finding of the specific gene responsible in 1993, mapped within a small segment of 4pl6.3, led to the establishment of predictive testing programmes from the mid 1980's. Several psychological investigations arose from these programmes including whether or not cognitive impairment was present presymptomatically in those at risk for HD, and whether those who requested testing were a self selected group. To date, the results of the neuropsychological studies have been conflicting and inconclusive. Methodological limitations and the stressfulness of predictive testing have probably contributed to the differing findings. The present study addressed the methodological flaws of previous studies and specifically controlled for the psychological experience of being at risk for a life threatening disease. To this end, 26 individuals at risk, but presyrrptomat ic, for HD were recruited from the Johannesburg Predictive Testing Programme. Subjects were administered a battery of psychological tests prior to molecular analysis. A carefully chosen control group, matched for age, sex, and education, and a group of individuals experiencing a life threatening illness (without CNS involvement) were administered the same battery of psychological tests. Molecular analysis confirmed 11 of the at risk were positive for the gene (HD+ group), and 15 negative (HD- group). Four way analysis of variance was conducted using the Bonferroni comparison of variances to detect group differences between the groups. The results indicated that stress negatively impacted upon the test performance of the HD- and stress group but not the HD+ group. The HD+ group showed mild impairment for declarative memory function. It was concluded that cognitive impairment was present prior to a clinical diagnosis of HD. A further outcome of the present study indicated that those who request predictive testing are self selected with regard to personality style and their goals in life. These findings have far reaching consequences for current and future predictive testing programmes in general.